MATERNAL KNOWLEDGE OF COMPLEMENTARY FEEDING AND ITS RELATIONSHIP WITH INFANT NUTRITIONAL STATUS IN A STUNTING LOCUS VILLAGE - Hidayat, Septi Maharani; Putri, Nindi Pramesthi Vardila; Hafidah, Lailatul (Universitas Kusuma Husada Surakarta, 2026)
Background: Nutritional problems in infants can negatively affect growth and development, including the risk of stunting. Maternal knowledge plays an important role in shaping feeding practices, yet many mothers still lack an adequate understanding of proper complementary feeding. This study aimed to examine the relationship between maternal knowledge of complementary feeding and infant nutritional status in a village with the highest stunting prevalence in Pamekasan Regency.Methods: A correlational analytic study design was employed, involving 54 mothers with infants aged 6–23 months selected through total sampling. Maternal knowledge was assessed using a closed-ended multiple-choice questionnaire, while infant nutritional status was evaluated using weight-for-age (WFA) Z-scores calculated with WHO Anthro version 3.2.2. Data were analyzed using the Spearman rank correlation test.Results: The results showed a weak, non-significant negative correlation (r = −0.212; ρ = 0.124). Conclusion: Although no significant association was found, maternal education on complementary feeding should be strengthened. Nutrition programs should also address broader determinants, such as food access, caregiving practices, and health service utilization, to improve infant nutritional outcomes in stunting areas.